Maternal and Child Health Using the Digitalization of the MCH Handbook Paciran Primary Health Care - Rizki Amalia; Endang Sulistiyani; Retno Aulia Vinarti; Adistha Eka Noveyani; Lutfi Agus Salim; Diah Indriani (Universitas STRADA Indonesia, 2025)
Background: Puskesmas is a Community Health Center which is a health service facility that aims to carry out public health efforts and first level individual care. Puskesmas prioritize promotive and preventive efforts to achieve optimal public health status. In the current industrial era 4.0, almost all activities have been digitized, the puskesmas should also have started to be digitized. Purpose: The data collection system at the Paciran Health Center still uses a manual system and patients often do not carry Maternal and Child Health (MCH) books. This research aims to accelerate the performance of the midwives at the Puskesmas so that it does not take up a lot of time and effort. And make it easier for the public so they don't have to carry the MCH handbook and see the examination results without opening the MCH handbook. Methods: The method of data collection used by the author in this research is observation, interviews and literature study. With the Java programming language with Netbeans IDE 8.0.2 as an editor and MySQL as a database. Results: The result of this research is that the data collection process becomes faster and more regular. Then the process of making reports can also be faster and neater. And also the patients are helped because they can know their progress, even though they do not carry or do not have the MCH book. Conclusion: This research aims to speed up the performance of midwives at the Paciran Community Health Center by digitizing the data recording system which was previously still manual. By using the Java programming language and MySQL database, this system allows the recording and reporting process to be faster and more structured. Apart from that, patients also find it easy to access examination results without having to carry a KIA book. The research results show that this digitalization increases the efficiency of services at the Community Health Center and makes it easier to access information for patients.